Global whole-genome comparison and analysis to classify subpopulations and identify resistance genes in weedy rice relevant for improving crops - Han, Zhenyun; Li, Fei; Qiao, Weihua; Zheng, Xiaoming; Cheng, Yunlian; Zhang, Lifang; Huang, Jingfen; Wang, Yanyan; Lou, Danjing; Xing, Meng; Fan, Weiya; Nie, Yamin; et al. (Frontiers in Plant Science, 2023)
Common weedy rice plants are important genetic resources for modern breeding programs because they are the closest relatives to rice cultivars and their genomes contain elite genes. Determining the utility and copy numbers of WRKY and NBS resistance-related genes may help to clarify their variation patterns and lead to crop improvements. In this study, the weedy rice line LM8 was examined at the whole-genome level. To identify the Oryza sativa japonica subpopulation that LM8 belongs to, the SNPs of 180 cultivated and 23 weedy rice varieties were used to construct a phylogenetic tree and a principal component analysis and STRUCTURE analysis were performed. The results indicated that LM8 with admixture components from japonica (GJ) and indica (XI) belonged to GJ-adm, with more than 60% of its genetic background derived from XI-2 (22.98%), GJ-tropical (22.86%), and GJ-subtropical (17.76%). Less than 9% of its genetic background was introgressed from weedy rice. Our results also suggested LM8 may have originated in a subtropical or tropical geographic region. Moreover, the comparisons with Nipponbare (NIP) and Shuhui498 (R498) revealed many specific SVs in the LM8 genome and fewer SVs between LM8 and NIP than between LM8 and R498. Next, 96 WRKY and 464 NBS genes were identified and mapped on LM8 chromosomes to eliminate redundancies. Three WRKY genes (ORUFILM02g002693, ORUFILM05g002725, and ORUFILM05g001757) in group III and one RNL-encoding NBS gene (ORUFILM12g000772) were detected in LM8. Among the NBS genes, the RPW8 domain was detected only in ORUFILM12g000772. This gene may improve plant resistance to pathogens as previously reported. Its classification and potential utility imply LM8 should be considered as a germplasm resource relevant for rice breeding programs.